Potential for virus transfer between the honey bees Apis mellifera and A. Cerana - Orlando Yañz (2018)
© 2016 International Bee Research Association. Viruses seem to play a key role in European honey bee, Apis mellifera health, and have a much broader host spectrum than previously thought. Few studies have investigated interspecific virus transfer within the genus Apis. The introduction of A. mellifera into Asia exposed endemic Apis species to the risk of obtaining new viruses or viral strains and vice versa. To investigate the potential for host shifts, virus prevalence and sequences were monitored over three years in single and mixed-species apiaries hosting introduced A. mellifera and endemic Apis cerana. Deformed wing virus (DWV), Israeli acute paralysis virus (IAPV), black queen cell virus (BQCV), and sacbrood virus (SBV) were found, but not KBV, VDV-1, ABPV, or CBPV. Virus infections and prevalence were generally lower in A. cerana compared to A. mellifera, and varied over the years. The sequence data provided evidence for interspecific transfer of IAPV, BQCV, and DWV, but SBV strains seem to be species specific. Prevalence and sequence results taken together indicate that interspecific transfers of viruses are rare, even if honey bees are kept in close proximity. We discuss the pattern observed in the context host specificity and resistance. Our understanding of the extent of these exchanges is limited by a lack of knowledge on the mechanisms of adaptation of viruses to different hosts.